MACRO- FEATURES AND DENSITY OF VARIOUS TIMBER SPECIES FROM PAPUA - MULIYANA ARIFUDIN; WAHYUDI (JURNAL KEHUTANAN PAPUASIA, 2020)
This research highlights diversity of macro-features and density of major timber species from Papua. Thirty-one species of air-dried timber with sample size of 13 cm × 6 cm × 4 cm gathered across Papua were used for density measurement and macro-features observation, cover of colors, grain orientation, and wood texture. The results showed that whitish and straw to yellow brown are dominant color of timber mostly harvested from Papua tropical forest. Their grain orientations are mostly straight, while their textures are medium. With regard to their density, Xantostemum spp is the heaviest timber having density of 1,25 g/cm3 while Alstonia scholaris is the lightest species of timber with density of 0.29 g/cm3. Therefore, majority Papua`s timber species studied are classified into light class species or low density timbers. Pulp and paper, veneer, plywood, flooring, meubels, indoor urnitures and handles or woody utensils are the potential uses of these timber species.